2008
DOI: 10.1039/b717750j
|View full text |Cite
|
Sign up to set email alerts
|

A rapid route to carbazole containing dendrons and phosphorescent dendrimers

Abstract: A convergent strategy for the synthesis of three generations of dendrons comprised of carbazole moieties is described. The procedure to build the dendrons involves an iterative palladium catalysed amination-debenzylation sequence using N-benzyl-3,6-dibromocarbazole. The three carbazolyl focussed dendrons are then attached to a reactive fac-tris[2-phenylpyridyl]iridium(III) core by a palladium catalysed amination to give the dendrimers. The three generations of dendrons have one, three, and seven carbazole unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 44 publications
1
61
0
Order By: Relevance
“…[12] Scheme 1 outlines the synthetic pathways for the formation of the four new dendrimers. Different strategies [21,22] were employed for the formation of the ''monodendronized'' (one dendron per ligand) and ''doubly dendronized'' (two dendrons per ligand) iridium(III) complexes. For the monodendronized dendrimers the iridium(III) complexes were first synthesized and then three dendrons were added in the final step to give dendrimers 2 and 5.…”
Section: Synthesismentioning
confidence: 99%
“…[12] Scheme 1 outlines the synthetic pathways for the formation of the four new dendrimers. Different strategies [21,22] were employed for the formation of the ''monodendronized'' (one dendron per ligand) and ''doubly dendronized'' (two dendrons per ligand) iridium(III) complexes. For the monodendronized dendrimers the iridium(III) complexes were first synthesized and then three dendrons were added in the final step to give dendrimers 2 and 5.…”
Section: Synthesismentioning
confidence: 99%
“…[29] In these materials there is one dendron per ligand of the core. We refer to them as ''single dendron'' materials and their structures are shown in Figure 1(a-c).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous report on dendrimers with fac-tris(2-phenylpyridyl)iridium(III) cores and the same dendrons it was found that the hole mobility (measured by time-of-flight) increased with increasing generation. 14 We were therefore motivated to determine whether the same affect would be observed in an OFET architecture where transport in the channel is dictated by the planar morphology, packing and hopping dynamics.…”
Section: Introductionmentioning
confidence: 99%